The role of Financial Technology in promoting Digital Transformation in Iraq for the period (2020-2023) - Ibtisam Ali Hussein; Suhaila Abdel Zahra Mastour; Nsreen Ghali Gasem (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Financial technology (FinTech) has become a key driver of digital transformation within contemporary financial systems worldwide. Specific Background: In Iraq, expanding electronic payments, mobile wallets, and digital banking tools between 2020 and 2023 reflects growing engagement with FinTech under the supervision of the Central Bank of Iraq. Knowledge Gap: Despite observable growth, empirical evidence remains limited regarding how FinTech indicators concretely support digital transformation within the Iraqi financial sector. Aims: This study aims to analyze the role of FinTech applications in promoting digital transformation in Iraq during 2020–2023. Results: Using a descriptive analytical approach and official data, the findings reveal significant increases in electronic payment infrastructure, mobile payment usage, and digital banking services, alongside persistent regional and competitive disparities. Novelty: The study provides a comprehensive indicator-based assessment linking FinTech adoption to digital transformation in Iraq. Implications: The results highlight the need for infrastructure expansion, regulatory support, and inclusive policies to strengthen digital financial transformation and financial inclusion.Keywords : Financial Technology, Digital Transformation, Electronic Payment Systems, Digital Banking, IraqHighlight : Electronic payment infrastructure expanded markedly, reflected by rising ATM, POS, and mobile transaction indicators. Mobile wallet usage increased substantially, with market concentration favoring a limited number of providers. Service adoption remained uneven, showing lower penetration in remote areas and among specific population groups.